Language Register in Digital Mobility Services: A Study of Online Transportation Platforms in Medan - Hutasuhut, Mahmud Layan; Siregar, Masitowarni; Maisaroh, Ajeng Dilla; Aulia, Delvi; Jenica, Martha (Universitas Negeri Medan, 2024)
This research discusses the use of language registers in online transportation platforms in Medan, especially Grab and Gojek. This research aims to identify the types of registers used and describe their use. Based on data analysis, three types of register were found: formal, consultative, and casual. Casual registers are the most dominant with 50%, followed by formal registers (37.5%) and consultative registers (12.5%). The use of these registers depends on the communication context, ranging from professional to informal, to create effective interactions between users and the platform. This study is expected to provide a theoretical contribution in understanding the dynamics of language registers in digital services as well as providing practical insights for the development of communication on bold platform.